Experimental study of steel wire mesh reinforced structural insulated panels against windborne debris impact - Chen, Wensu; Hao, Hong; Meng, Q. (2017)
Wind speed has been increasing with climate change in recent decades, which has led to devastating damages in the recent strong wind events such as Cyclone Yasi in Queensland (2011), Typhoon Haiyan in Philippines (2013) and Cyclone Marcia in Queensland with wind gusts of almost 300 km/h (2015). These events caused loss of lives and hundred millions of dollars in properties. Windborne debris impact is deemed as a major cause of damage to the building envelop and the occupants inside the building in strong wind events (Minor et al. 1972). The dominant opening created by the windborne debris impact might cause internal pressurization (Walker 1991) and trigger roof lift-up and even structural collapse. Therefore, the research on the penetration resistance capacity of building envelop is important for the protection of properties and lives.